Socio-cultural conservation strategies and sustainable tourism development in communal group ranches in Laikipia County, Kenya - Nzomo, Cosmas; Bitok, Kipkosgei; Muthengi, Sisinio (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: This study investigates the effects of socio-cultural conservation strategies on sustainable tourism development in communal group ranches in Laikipia County, Kenya. This study examines how social inclusion, cultural preservation, local entrepreneurship, and product diversification contribute to sustainable tourism outcomes. Methods: An embedded mixed-method design was applied, combining surveys of 392 respondents—including ranch members, leaders, and tourists—with qualitative interviews. Quantitative analysis used SPSS (v.22) for descriptive statistics, regression, and ANOVA, while qualitative data were analyzed thematically. Results: The findings show that socio-cultural strategies collectively have a significant effect on sustainable tourism (R = 0.345, R² = 0.119, F = 8.771, p < 0.001). Social inclusion of minority groups was the only significant predictor (? = 0.239, p = 0.001). Cultural preservation, entrepreneurship, and product diversification have positive but insignificant effects, which are likely constrained by governance, infrastructure, and financial barriers. Qualitative evidence confirmed community pride in cultural events and crafts but also revealed limited benefit distribution and weak inclusion of marginalized groups. Conclusion: Socio-cultural conservation strategies positively influence sustainable tourism, but with modest explanatory power. Effective governance, stronger policy frameworks, and targeted financial support are required to enhance the role of women in agriculture. Limitations: The findings are specific to Laikipia County and may not be generalizable. Self-reported data may also introduce biases. Contribution: This study provides empirical evidence of conservation-tourism linkages in Africa, highlighting the central role of social inclusion. It offers practical insights for policymakers, conservationists, and development actors seeking to align cultural heritage with sustainable tourism and SDGs.